Experiencing Uncertainty and Feelings of Anxiety in Cross-Cultural Project Teams - Mustaniemi, Terhi (My University, 2003)
The objective of the research is to explore the functioning and role of experiencing uncertainty and anxiety in cross-cultural project teams. Moreover, the objectives are to name instances, which can result in uncertainties and anxieties, and to explore some cultural differences dealing with these emotions. These objectives were achieved by analysing 62 in-depth interviews of project members. The projects consisted of members from countries, which were Finland, Germany, France, UK and USA. The research’s methodological approach is qualitative. The frame for research consists of some definitions of concepts in terms of the theme for research, and discussions about prior researches of uncertainty experiments and feelings of anxiety. Moreover, as presented by previous theories, uncertainty and anxiety are treated in parallel with each others. In the results of the research analysis and in the conclusion, some former theories are examined in accordance to the results of this research. The main finding of the research is a model presenting the instances and functioning of uncertainties and anxieties. It consists of three categories and their sub-categories, which can result in these emotions. Moreover, it consists of four background-variables, which have an affect on the three main categories. The figure presents some matters, which have an affect on uncertainties and anxieties, and it also implies some issues of cultural differences, which can be considered as troublesome in cross-cultural interactions in team work situations.
Keywords: uncertainty; anxiety; cross-cultural; team; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|